The Role of Individual Differences Theory in an Election - Nwonu, Clifford O.; Ineji, Patrick (ESUT JOURNAL OF SOCIAL SCIENCES, 2023)
Most political scientists agree that the mass media have a profound impact on voting behavior. One author asserts that few would argue with the notion that the institution of the mass media is important to contemporary politics and in the transition to liberal democratic politics that the media is the key battleground. In the 2011 general election in Nigeria especially that of the. presidential election: the mass media played a wonderful role in sensitizing and mobilizing the electorates. The study of Enugu in Enugu State and Calabar in Cross River State showed that among the cross section of voters in these two states interviewed and mail questionnaires administered on 80 participants (40 interviewees and 40 respondents) to solicit information on their feelings and what actually made them to come out enmasse to vote and on the influence of social relationships and other factors on voters’ choice. It was discovered that the media alone was the significant and determining factor in the choice of candidate especially that of the president during the April 16 election. It was discovered that other factors, both social and psychological also influenced voters’ choice. Among them include long and short term influences on political orientation and influence of social groups on political outcomes which include the effects of ethnic groups, religious and gender influences.